Semut sebagai Ide Dasar Penciptaan Drawing dengan Teknik Cross Contour dan Pointilis - Joseph Saleh Hidayat Gulo; Nelson Tarigan (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This work was created based on the author's interest in ants, starting from their lifestyle, how they find food, size, and most importantly their shape. The author likes the shape of an ant's body which, when observed closely, turns out to have its own uniqueness in each type that is often forgotten due to its small size. The author is interested in raising the object of ants as a work of creation because the author wants to reveal the shape of ants that other people rarely realize. The work that the author created was made using the cross contour and pointillist techniques. The author uses a combination of these two techniques because these two techniques are very flexible for the author to use in drawing the shape of an ant's body, without the effects of color, only pure black and white shapes. The author created 15 works of art that display realistic shapes of 15 types of exotic ants in the world.